An evaluation of the implementation of Mercedes Benz production system (MPS) and the employee change readiness at Mercedes Benz commercial vehicles South Africa - McAllister, Rozane Ronardo (Rhodes University, Faculty of Commerce, Rhodes Business School, 2015)
The evaluation report section describes the evaluation of the implementation of Mercedes Benz Production System (MPS) at Mercedes Benz Commercial Vehicles, which is a division of Mercedes Benz South Africa's manufacturing plant situated in East London. The section evaluates the changes the implementation of MPS brought to the Key Performance Indicators (KPI'S) of the division and evaluates the change readiness of the employees in the division prior to the change. The change implementation was initiated by the management of MBCV as a strategic organisational change to bring about continuous improvement to the KPI's of the organisation. These KPI's are Safety, Quality, Delivery, Cost and Morale (SQDCM). The reason behind the change at the time was deemed critical to MBCV in order to meet the annual KPI targets and remain cost competitive and sustainable. The evaluation report further describes the results of the change with regards to the organisational KPI's and the level of employee change readiness which was conducted through a questionnaire survey. A brief literature review is included in the Evaluation Report under section one describing key concepts about Production Systems, Lean Manufacturing and Change Management. The evaluation section includes recommendations based on the results of the research findings and ends with a conclusion. The literature review section explores the literature that supports production systems, lean manufacturing and change management concepts, its definitions, importance and benefits. The literature review describes and critiques key concepts of the research such as productions systems, MPS in particular, lean manufacturing concepts and related change management topics relevant to the research. The literature review defines production systems and the concepts of lean manufacturing, highlighting the benefits of the concepts to enhance organisations' manufacturing capabilities. An integrated part of lean manufacturing is people and the implementation of lean manufacturing into an organisation requires change management theories therefore key understanding in this particular research was to discuss change management concepts, in particular, employee change readiness. The literature will discuss different tools to assess employee change readiness and from this develop an employee change readiness tool. The change management concepts evaluated change readiness and the consequences if organisations are not ready for change. The research methodology section describes how that the research was conducted in two phases, one to evaluate the implementation of MPS with regards to the organisational KPI's (SQDCM). This was assessed through reports from projects and presentations made by the project teams on improvements of the organisational KPI's. The second phase evaluated the change readiness of the employees prior to the implementation of MPS. This phase of the research was intended to retrieve quantitative data with an adapted questionnaire which was distributed to employees. To evaluate the change readiness, a change model known as ADKAR was used as an evaluation instrument. The modified ADKAR questionnaire was distributed to employees in hard copies and completed during a weekly team meeting. The results were summarised and descriptive statistics were used to analyse the final results. Microsoft Excel (2010 version) was used to illustrate and display the graphs. Section three discussed the research methodology in more detail. The study shows that although there were some positive changes that came from the implementation of MPS in MBCV, especially to the following KPI's (Safety, Quality, Delivery and Cost), real consideration should be given to employee morale and the level of change readiness of MBCV employees.
Keywords: Daimler-Benz Aktiengesellschaft; Organizational change -- South Africa; Organizational behavior -- South Africa; Employees -- Attitudes; Continuous improvement process -- South Africa